2020
DOI: 10.3389/fpsyt.2020.585686
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Effects of Corona Measures on Patients With Dementia, Mild Cognitive Impairment and Subjective Cognitive Decline

Abstract: Background: The recent COVID-19 pandemic is not only a major healthcare problem in itself, but also poses enormous social challenges. Though nursing homes increasingly receive attention, the majority of people with cognitive decline and dementia live at home. We aimed to explore the psychosocial effects of corona measures in memory clinic (pre-)dementia patients and their caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
76
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 34 publications
9
76
0
1
Order By: Relevance
“…Higher variations in social support service hours significantly predicted increased levels of anxiety in people with NCD [ 50 ]. Similar observations were reported by an additional survey where over 30% of symptomatic patients were unable to go to day care or community care services [ 20 ]. Cohen et al [ 23 ] likewise observed that there was a high rate of discontinuation of rehabilitation during the epidemic with 76% of elderly patients with dementia having discontinued physical therapy, 91% occupational therapy, and 77% cognitive rehabilitation.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Higher variations in social support service hours significantly predicted increased levels of anxiety in people with NCD [ 50 ]. Similar observations were reported by an additional survey where over 30% of symptomatic patients were unable to go to day care or community care services [ 20 ]. Cohen et al [ 23 ] likewise observed that there was a high rate of discontinuation of rehabilitation during the epidemic with 76% of elderly patients with dementia having discontinued physical therapy, 91% occupational therapy, and 77% cognitive rehabilitation.…”
Section: Resultssupporting
confidence: 86%
“…Another cross-sectional study conducted by telephone survey on 139 PLWD showed that 54.7% of them experienced worsened or emerging behavioral disturbances with agitation, aggression, apathy, and depression [ 14 ]. Results from a survey cohort on 121 symptomatic patients with NCD showed that almost half of patients reported an increase of one or more psychological symptoms (e.g., loneliness, anxiety, uncertainty and depression) and over 30% experienced social isolation [ 20 ]. Increases in behavioral symptoms, such as apathy, changes in sleeping behavior and aggression were also noted.…”
Section: Resultsmentioning
confidence: 99%
“…The disruption in routine activities has produced a significant overall decline and a reduced autonomy in daily living activities in care recipients, as reported by their caregivers [34,35]. Coherently, worries of faster cognitive decline have been reported both in patients and in caregivers, and also in cognitively normal individuals, all experiencing increased psychological symptoms [36]. In fact, the most consistent finding reported during the pandemic period regards a higher rate of neuropsychiatric symptoms due to social isolation in people with dementia [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, 24% of community-dwelling older adults were estimated to be socially isolated [ 6 ]. Recently, these numbers have increased rapidly across the globe due to the COVID-19 pandemic, especially among people with cognitive impairment [ 7 ]. In a recent Dutch study, more than half of the community-dwelling participants with cognitive decline reported not having any face-to-face contact with friends (52%) or family (57%) during the pandemic [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, these numbers have increased rapidly across the globe due to the COVID-19 pandemic, especially among people with cognitive impairment [ 7 ]. In a recent Dutch study, more than half of the community-dwelling participants with cognitive decline reported not having any face-to-face contact with friends (52%) or family (57%) during the pandemic [ 7 ]. This kind of social isolation can negatively affect their mental and physical health [ 8 , 9 ], mortality [ 10 ], well-being, and quality of life [ 11 ].…”
Section: Introductionmentioning
confidence: 99%